Coherent nanophotonic electron accelerator - Chlouba, Tomas; Shiloh, Roy; Kraus, Stefanie; Brückner, Leon; Litzel, Julian; Hommelhoff, Peter (Nature, 2023)
Particle accelerators are essential tools in a variety of areas of industry, science and medicine1,2,3,4. Typically, the footprint of these machines starts at a few square metres for medical applications and reaches the size of large research centres. Acceleration of electrons with the help of laser light inside of a photonic nanostructure represents a microscopic alternative with potentially orders-of-magnitude decrease in cost and size5,6,7,8,9,10,11,12,13,14,15,16. Despite large efforts in research on dielectric laser acceleration17,18, including complex electron phase space control with optical forces19,20,21, noteworthy energy gains have not been shown so far. Here we demonstrate a scalable nanophotonic electron accelerator that coherently combines particle acceleration and transverse beam confinement, and accelerates and guides electrons over a considerable distance of 500 μm in a just 225-nm-wide channel. We observe a maximum coherent energy gain of 12.3 keV, equalling a substantial 43% energy increase of the initial 28.4 keV to 40.7 keV. We expect this work to lead directly to the advent of nanophotonic accelerators offering high acceleration gradients up to the GeV m−1 range utilizing high-damage-threshold dielectric materials22 at minimal size requirements14. These on-chip particle accelerators will enable transformative applications in medicine, industry, materials research and science14,23,24.<br
Keywords: Nanophotonics and plasmonics; Photonic devices; Ultrafast photonics